2004
DOI: 10.1111/j.1440-1746.2002.03234.x
|View full text |Cite
|
Sign up to set email alerts
|

Gastric cancer with metastasis to the gingiva

Abstract: The present case report describes a gastric cancer which showed unusual metastasis in the oral region. A 56-year-old male patient underwent total gastrectomy and splenectomy due to advanced gastric cancer in the upper third of the stomach. Fifteen months later, he presented with anorexia and gingival swelling of durations of approximately 3 and 1 month, respectively. The gastric tumor was histologically a signet ring cell and a poorly differentiated cancer with a moderate degree of vascular invasion. Biopsy sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 16 publications
(37 reference statements)
0
14
0
1
Order By: Relevance
“…indicating that the route of metastasis might be hematogenous [9], our case also showed moderate venous invasion by gastric carcinoma cells in the resected stomach, which could explain the oral lesion. In this regard, we agree with other authors who consider patients with oral metastases as having a poor prognosis because of aggressive disease, but it is unclear whether our patient's disease was really widespread at the time of its first manifestation in the gingiva [9-11]. …”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…indicating that the route of metastasis might be hematogenous [9], our case also showed moderate venous invasion by gastric carcinoma cells in the resected stomach, which could explain the oral lesion. In this regard, we agree with other authors who consider patients with oral metastases as having a poor prognosis because of aggressive disease, but it is unclear whether our patient's disease was really widespread at the time of its first manifestation in the gingiva [9-11]. …”
Section: Discussionmentioning
confidence: 70%
“…Our case is interesting because the metastatic lesion of the palate was diagnosed before the discovery of the primary tumour, whereas most other previously published reports involve gastric cancers that were already known or simultaneously discovered at the time of the manifestation of the oral lesion [4,5,8,9]. Only Lopez and Arjona have described a case like ours in which the patient developed a gingival lesion before any clinical or pathological evidence of the primary tumour was found [6,7].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Elkhoury et al reviewed the English literature from 1991 to October 2003 and found an additional 22 cases of reported metastases to the gingiva 7 . A review of the English literature from October 2003 to November 2007 revealed an additional 8 cases of metastases to the gingiva 1,5,8,15,16,18,21,22 to bring the total number since 1916, including the present case, to 117 cases. These 117 cases, listed according to the primary site of metastases, are summarized in Table 1.…”
Section: Discussionmentioning
confidence: 92%
“…Cases of intraoral metastasis have been reported from primary chondrosarcoma of femur,[9] adenocarcinoma of lung,[10] gastric cancer[11] and hypernephroma. [12] This is a case report of a patient with adenocarcinoma of the lung which metastasized to left posterior buccal and lingual gingiva.…”
Section: Introductionmentioning
confidence: 99%